2016
DOI: 10.1155/2016/5704963
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Duration of Monitoring for Atrial Fibrillation in Cryptogenic Stroke: A Nonsystematic Review

Abstract: Atrial fibrillation (AF) is the most common form of cardiac arrhythmias and an independent risk factor for stroke. Despite major advances in monitoring strategies, clinicians tend to miss the diagnoses of AF and especially paroxysmal AF due mainly to its asymptomatic presentation and the rather limited duration dedicated for monitoring for AF after a stroke, which is 24 hours as per the current recommended guidelines. Hence, determining the optimal duration of monitoring for paroxysmal atrial fibrillation afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 91 publications
(115 reference statements)
1
24
0
Order By: Relevance
“…It is unclear whether our practice patterns, patient demographics, and health care system characteristics are generalizable to other regions, although we know, based on census data, that our region is representative of the United States with regard to median age, percentage of black persons, median household income, and percentage of the population below the poverty level (Table 4). Second, with respect to detection of paroxysmal AF, it is known that transthoracic echocardiogram and a single ECG are not sensitive 8. A limitation of our study is that we did not have data on the frequency of telemetry use on the inpatient stroke unit for all study periods or on discharge with Holter or 30‐day event monitors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is unclear whether our practice patterns, patient demographics, and health care system characteristics are generalizable to other regions, although we know, based on census data, that our region is representative of the United States with regard to median age, percentage of black persons, median household income, and percentage of the population below the poverty level (Table 4). Second, with respect to detection of paroxysmal AF, it is known that transthoracic echocardiogram and a single ECG are not sensitive 8. A limitation of our study is that we did not have data on the frequency of telemetry use on the inpatient stroke unit for all study periods or on discharge with Holter or 30‐day event monitors.…”
Section: Discussionmentioning
confidence: 96%
“…A recent meta‐analysis found that increasing use of antiplatelet drugs and antihypertensive medications was associated with this decline,8 although a causal relationship clearly cannot be determined. It may also be speculated that carotid endarterectomy and anticoagulation have reduced recurrent strokes in patients with high‐grade carotid stenosis and AF, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are other proposed schemes for prediction of paroxysmal AF following an ischemic stroke. One of the best one studied is the iPAB score, which includes a personal history of arrhythmia or antiarrhythmic drug use, atrial dilatation, and elevation of brain natriuretic peptide …”
Section: Which Patients Will Benefit From Prolonged Ecg Monitoring?mentioning
confidence: 99%
“…One of the best one studied is the iPAB score, which includes a personal history of arrhythmia or antiarrhythmic drug use, atrial dilatation, and elevation of brain natriuretic peptide. 15 The evidence regarding the monitoring time to be employed in patients with CS for detecting AF is still inconclusive. A recent consensus document recommends "extended ECG monitoring" in patients with CS to detect undiagnosed AF.…”
mentioning
confidence: 99%